OGPA: a novel indicator hinting at the academic performance of Chinese vocational college students using stepwise regression - Chen, Juntao; Wei, Shuling; Zhou, Xiaodeng; Yao, Jiahua; Tang, Su-Kit (Frontiers in Education, 2024)
Studying the factors influencing the academic performance of higher education students has been a major focus of attention for research scholars across the world. However, empirical research literature specifically addressing this topic in the context of Chinese higher vocational colleges remains limited. This study aims to construct a novel indicator that hints at the academic performance of Chinese college students. Using approximately 2,270 records of students majoring in economics and management from the 2016 to 2020 academic years, this comprehensive study analyzed various aspects of their academic and extracurricular performance, encompassing 33 variables. These variables ranged from fundamental demographic characteristics to essential academic metrics like Gaokao Scores (GKs), College English Test 4 (CET4), academic achievements, participation and outcomes in skill competitions, student honors received, challenges faced, and involvement in volunteer services. This study found that (1) GKs, CET4, National Computer Rank Examination (NCRE), Total Scholarship (TSS), Outstanding Student (OS), Outstanding Student Leader (OSL), General Difficulty Student (GDS), and Volunteer Service Hours (VSHs) all show a significant positive correlation with academic performance and (2) age was negatively correlated with academic performance. In addition, the study also found that the effect of volunteer service on academic performance showed a folded relationship between “valley” and “peak.” These findings provide a source of ideas and empirical references for college education administrators and educational policymakers when revising or developing policy documents.